2014
DOI: 10.1111/anu.12081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental Azomite in diets on growth, immune function and disease resistance of white shrimp (Litopenaeus vannamei)

Abstract: This study was conducted to evaluate effects of dietary Azomite, a natural mineral of volcanic ash, on growth performance, digestive enzyme activities, serum non-specific immunity and disease resistance of white shrimp (Litopenaeus vannamei). Graded levels of 0.0 g kg À1 (control group), 2.0, 4.0, 6.0 and 8.0 g kg À1 Azomite were supplemented in basal diet to feed shrimps. After 6 weeks feeding, weight gains of the 2.0 and 4.0 g kg À1 Azomite groups were significantly higher than that of the control group (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Over last two decades, azomite widely used as a feed additive in aquaculture as well as in livestock and organic agriculture. Some research findings reported that azomite improves the feed quality, weight gain, nutrient digestibility, feed conversion ratio and immunity in shrimp, tilapia and catfish (Liu et al, 2009(Liu et al, , 2011Musthafa et al, 2016;Tan et al, 2014). Azomite also increases the activity of digestive enzymes in tilapia Ctenopharyngodon idellus (Liu et al, 2009;Tan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over last two decades, azomite widely used as a feed additive in aquaculture as well as in livestock and organic agriculture. Some research findings reported that azomite improves the feed quality, weight gain, nutrient digestibility, feed conversion ratio and immunity in shrimp, tilapia and catfish (Liu et al, 2009(Liu et al, , 2011Musthafa et al, 2016;Tan et al, 2014). Azomite also increases the activity of digestive enzymes in tilapia Ctenopharyngodon idellus (Liu et al, 2009;Tan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have evaluated the effects of different diets on the activity of proteases, carbohydrases and lipases in penaeids (Shao et al, 2017;Tan et al, 2014;Xu, Pan, Sun, & Huang, 2013).…”
mentioning
confidence: 99%
“…In Vibrio alginolyticus ‐challenged shrimp, azomite supplementation increased survival rates (Tan et al. ). Echeverry et al.…”
Section: Resultsmentioning
confidence: 99%
“…The basal diet was supplemented with azomite (0.25% or 0.50%) or sea salt (0.5% or 1.0%). The supplementation levels were based on previously published studies (Nandeesha et al 2000;Gangadhara et al 2004; Harpaz et al 2005;Liu et al 2009Liu et al , 2011Tan et al 2014;Musthafa et al 2016). The levels of other ingredients were constant for all diets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation